1922
DOI: 10.1136/bmj.1.3205.872
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Cause of Death From Cancer

Abstract: AN UNUSUAXJ CAUSE OF DEATH FROM CANCER. )I~ã nd apparently composed of pleura which is thickened in that region. Through this clear area the details of the ribs and scapula can be made'out.; tllere is very little evidence of dMtail of 'the lung. Tlle lower margin is irregular and ill defined, and slhows strands of denser tissue with clear areas between. The general 'appearance is strongly suggestive of air in the pleural cavity. It has not tlle typical appearance of a large pneumothorax, and is more typical o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

1927
1927
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Primary treatment involved surgery in five cases (25%) [ 11 , 15 ], radiotherapy in one case (5%) [ 6 ], combination therapy with surgery and radiation in five cases (25%) [ 8 , 9 , 12 , 13 , 16 ], and a combination of surgery with chemoradiation in two cases (10%) [ 1 ], including current case. Two patients had tracheostomy performed for symptom relief [ 3 , 14 ]. Most cases (80%) had cardiac metastases discovered within two years after the initial diagnosis, except one, where metastatic disease to the heart was diagnosed five years later [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary treatment involved surgery in five cases (25%) [ 11 , 15 ], radiotherapy in one case (5%) [ 6 ], combination therapy with surgery and radiation in five cases (25%) [ 8 , 9 , 12 , 13 , 16 ], and a combination of surgery with chemoradiation in two cases (10%) [ 1 ], including current case. Two patients had tracheostomy performed for symptom relief [ 3 , 14 ]. Most cases (80%) had cardiac metastases discovered within two years after the initial diagnosis, except one, where metastatic disease to the heart was diagnosed five years later [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tumors involving the heart and pericardium are far more likely to be secondary (metastatic) than primary, occurring in up to 18.3% of patients with metastatic disease [ 2 ]. Cardiac metastasis of laryngeal cancer is a rare condition, with one of the earliest reports of infiltrative cardiomyopathy secondary to laryngeal carcinoma written by Linell et al in 1922 [ 3 ], and only several cases reported in the literature over the past century. We report a case of laryngeal squamous cell carcinoma (SCC) with subsequent metastatic disease to the heart.…”
Section: Introductionmentioning
confidence: 99%
“…Vetenskaparna har då inte alltid varit helt konsekventa i sin sekularisering*. Man bygger inte bara på naturvetenskap och 45 Jfr Linell (2017a). Generativismen har stora problem att förklara hur ett så abstrakt språk som teorin antar "finns", kan ha utvecklats evolutionärt.…”
Section: En Sekulariserad Livs-och Världsåskådningunclassified
“…Chomsky har i en intervju citerad av MacNeilage (2008: 3) deklarerat att språket inte kan förklaras; "det tycks bara vara så att det finns". Generativismen är emellertid inte ensam bland språkteorier om att ha vetenskapsteoretiska problem (se vidare Linell, 2017a). Somliga problem delas med strukturalismen i stort (t.ex.…”
Section: En Sekulariserad Livs-och Världsåskådningunclassified
“…His subsequent MD thesis, awarded in 1920, concerned the anatomy of the peripheral nervous system 53 . He showed some early interest in pathology, publishing an autopsy report of carcinoma of the larynx 54 , but had no formal training in pathology. In 1923 he was recruited to the University of Toronto to teach neuroanatomy 55 .…”
Section: Development Of Neuropathology In Toronto 1930s-1950smentioning
confidence: 99%